Combination Strategies to Augment Immune Check Point Inhibitors Efficacy - Implications for Translational Research - Varayathu, Hrishi; Sarathy, Vinu; Thomas, Beulah Elsa; Mufti, Suhail Sayeed; Naik, Radheshyam (Frontiers in Oncology, 2021)
Immune checkpoint inhibitor therapy has revolutionized the field of cancer immunotherapy. Even though it has shown a durable response in some solid tumors, several patients do not respond to these agents, irrespective of predictive biomarker (PD-L1, MSI, TMB) status. Multiple preclinical, as well as early-phase clinical studies are ongoing for combining immune checkpoint inhibitors with anti-cancer and/or non-anti-cancer drugs for beneficial therapeutic interactions. In this review, we discuss the mechanistic basis behind the combination of immune checkpoint inhibitors with other drugs currently being studied in early phase clinical studies including conventional chemotherapy drugs, metronomic chemotherapy, thalidomide and its derivatives, epigenetic therapy, targeted therapy, inhibitors of DNA damage repair, other small molecule inhibitors, anti-tumor antibodies hormonal therapy, multiple checkpoint Inhibitors, microbiome therapeutics, oncolytic viruses, radiotherapy, drugs targeting myeloid-derived suppressor cells, drugs targeting Tregs, drugs targeting renin-angiotensin system, drugs targeting the autonomic nervous system, metformin, etc. We also highlight how translational research strategies can help better understand the true therapeutic potential of such combinations.